Global research trends in tryptophan metabolism and cancer: a bibliometric and visualization analysis (2005–2024) - Ma, Huanhuan; Ding, Ran; Wang, Junwen; Du, Guangying; Zhang, Yun; Lu, Qiuchen; Hou, Yingyue; Chen, Haosong; Jiao, Hongguan (Frontiers in Oncology, 2025)
BackgroundIn recent years, tryptophan metabolism has gained increasing attention for its pivotal role in shaping the tumor immune microenvironment and promoting cancer progression. As a result, it has become a central topic in cancer metabolism and tumor immunology. This study applies a comprehensive bibliometric approach to analyze global research trends in tryptophan metabolism within the context of cancer. By identifying emerging hotspots, leading contributors, and patterns of international collaboration, this work aims to provide meaningful insights to guide future therapeutic strategies targeting metabolic pathways in oncology.MethodsA systematic literature search was performed using the Web of Science Core Collection to retrieve publications related to tryptophan metabolism in cancer from 2005 to 2024. Bibliometric and visual analyses were conducted using CiteSpace, VOSviewer, and Python to examine publication trends, national and institutional contributions, author productivity, journal influence, co-citation networks, and keyword co-occurrence patterns.ResultsA total of 1,927 publications were identified, authored by 11,134 researchers from 70 countries and published in 781 academic journals. The volume of publications showed a steady increase, peaking in 2021. The United States and China emerged as the dominant contributors, excelling in both research output and international collaboration. Dietmar Fuchs was identified as the most prolific author, with 61 publications. The Medical University of Innsbruck was the leading institution, with 144 publications. Frontiers in Immunology demonstrated strong citation performance and academic impact. Co-citation and keyword analysis revealed key research themes, including “IDO (indoleamine 2,3-dioxygenase),” “tryptophan catabolism,” “cancer,” and “dendritic cells,” as well as emerging topics such as “gut microbiota,” “tumor microenvironment,” “aryl hydrocarbon receptor,” and “cancer immunotherapy.”ConclusionThis study highlights the growing significance of tryptophan metabolism research in cancer, underlining the complex interactions between metabolic pathways and immune responses. Further investigations are needed to explore the therapeutic potential of these metabolic pathways, which could lead to novel cancer treatment strategies.